Circulating eNampt and resistin as a proinflammatory duet predicting independently mortality in critically ill patients with sepsis: A prospective observational study. (July 2019) - Karampela, Irene; Christodoulatos, Gerasimos Socrates; Kandri, Evangelia; Antonakos, Georgios; Vogiatzakis, Evaggelos; Dimopoulos, George; Armaganidis, Apostolos; Dalamaga, Maria
Highlights: Serum eNampt and resistin are elevated in critically ill septic patients. Sustained elevation of eNampt and resistin is associated with severity of sepsis. Their lower kinetics in the first week of sepsis independently predict mortality. eNampt outperformes classic biomarkers in discriminating sepsis from septic shock. Abstract: Background: The adipocytokines eNampt and resistin are involved in the regulation of inflammation exerting pro-inflammatory actions. Our aim was to jointly investigate whether circulating eNampt and resistin, and their kinetics predict 28-day mortality of sepsis. Methods: In a prospective study, serum eNampt and resistin were determined in 102 critically ill patients fulfilling the diagnostic criteria of SEPSIS-3, at enrollment and one week after, and in 102 healthy controls matched on age, gender and month of diagnosis. Results: Serum eNampt and resistin were significantly higher in septic patients than controls (p < 0.001), and higher in septic shock compared to sepsis (p < 0.001). Both eNampt and resistin decreased significantly during the first week of sepsis (p < 0.001). However, patients with septic shock presented a sustained elevation of eNampt and resistin compared to patients with sepsis. Both adipocytokines were positively correlated with sepsis severity scores and lactate. Baseline eNampt was a better discriminator of sepsis and septic shock compared to C-reactive protein and procalcitonin. Serum eNampt and resistin were higher in nonsurvivors than in survivors during the first week of sepsis. Prolonged and sustained elevation of both eNampt and resistin, as reflected by a lower percentage change from their baseline values, was independently associated with 28-day mortality (HR: 0.05, 95% C.I. 0.01–0.28, p = 0.001; HR: 0.19, 95% C.I. 0.07–0.50, p = 0.001, respectively), after adjustment for significant clinical and laboratory biomarkers. Conclusion: Circulating eNampt and resistin, and their kinetics may represent useful diagnostic and prognostic biomarkers in critically ill septic patients. More prospective studies are needed to elucidate their ontological and pathophysiological role in sepsis.